Surviving Dynastic Change: The High Nobility during the War of the Spanish Succession (1701–15) - López Anguita, José Antonio (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2020)
The accession of the House of Bourbon to the Spanish throne after the death of the last Habsburg king, Carlos II, in 1700 brought important changes for the court high nobility. Historians have seen Philip V’s reign as the beginning of the titled nobility’s withdrawal from the front line of politics. The process, encouraged by the Bourbon’s reformism during the War of the Spanish Succession, was carried out by the nobility in several ways. This article will analyze the careers of aristocrats such as Pedro Manuel Colón de Portugal and José Solís y Valderrábano, dukes of Veragua and Montellano, and Rodrigo Fernández Manrique de Lara, Count of Frigiliana, who adapted their actions to the new regime’s politics in order to enjoy the patronage of new political actors. They took part in royal court circles to achieve important political positions without renouncing their right to oppose change through strategies linked to the political culture of the previous dynasty: for example, their involvement in political gatherings and their absence in important court celebrations. My article posits that, although the relations between the House of Bourbon and these nobles were undoubtedly complex and ambivalent, as their career at court shows, they were far more nuanced and fluid than has previously been revealed.